An Evaluation of an Extended Intervention to Reduce Plagiarism in Bachelor of Nursing Students. Issue 2 (March 2020) - Smedley, Alison; Crawford, Tonia; Cloete, Linda
Abstract : Abstract: Pre- and postintervention surveys of first-year nursing students were undertaken to establish the students' knowledge of plagiarism following implementation of an online library-based Academic Integrity Module and the use of plagiarism detection software. Knowledge and understanding of plagiarism improved, but students' ability to paraphrase remained poor. Students entering postsecondary educational institutions require ongoing support and learning opportunities to improve their skills in paraphrasing and referencing to avoid plagiarism. Abstract : Supplemental digital content is available in the text.